PENGGUNAAN MODEL KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION UNTUK MENINGKATKAN KETERAMPILAN MENULIS PUISI PADA SISWA KELAS V SD NEGERI 1 JLEGIWINANGUN TAHUN AJARAN 2015/2016 - muawanah, naelatul (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Use of Cooperative Integrated Reading and Composition Cooperative Learning Model to Improve Writing Skills of Poem for the Fifth Grade Students. The objective of this research is to improve poem writing skills through the use of Cooperative Integrated Reading and Composition cooperative learning model. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Subjects of the research were 24 students, consisting of 16 boys and 8 girls, of fifth grade students in SD Negeri 1 Jlegiwinangun in the academic year of 2015/2016. The results of this research show that the application of Cooperative Integrated Reading and Composition cooperative learning model can improve poem writing skills for the fifth grade students of SD Negeri 1 Jlegiwinangun in the academic year of 2015/2016.Keywords: CIRC, writing skills, poem